2008
DOI: 10.1089/cpb.2007.0035
|View full text |Cite
|
Sign up to set email alerts
|

Induced Attitude Change on Online Gaming among Adolescents: An Application of the Less-Leads-to-More Effect

Abstract: The negative impact of Internet use on adolescents has received much popular attention and has also become a popular research topic. How to induce adolescent players to change their attitudes toward online gaming is one of the most important issues in online gaming addiction. The present study is based on the less-leads-to-more effect of dissonance theory. Experimental research was conducted to examine the effects of rewards and decision freedom on attitude change toward online gaming among adolescents conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…This is awkward, given the wealth of literature (eg, McMillan and Hwang provide an overview [49]) documenting the importance of user control in shaping user experience [45,50]. Furthermore, previous research identified the role of user control (ie, freedom of choice) in attitude change [51] and intention to use [12,14]. The effect of user control on e-loyalty is in line with previous studies and is expected to be mediated through user perceptions [12,52].…”
Section: Discussionmentioning
confidence: 99%
“…This is awkward, given the wealth of literature (eg, McMillan and Hwang provide an overview [49]) documenting the importance of user control in shaping user experience [45,50]. Furthermore, previous research identified the role of user control (ie, freedom of choice) in attitude change [51] and intention to use [12,14]. The effect of user control on e-loyalty is in line with previous studies and is expected to be mediated through user perceptions [12,52].…”
Section: Discussionmentioning
confidence: 99%
“…The sample consisted of 64 single students and young adults (31 women and 33 men; aged 18–31 years, mean age = 20.9, SD = 2.9) from southern Taiwan who were members of online dating services, as determined by a screening questionnaire. They were recruited from the subject pool of an adolescent online gaming survey supported by the National Science Council of Taiwan (Chiou, ) and participated in this study in exchange for $NT100 (approximately $US3.3). Participants were randomly assigned to an accuracy‐incentive condition.…”
Section: Methodsmentioning
confidence: 99%